Detection of Brucella spp. in Stretched Curd Cheese as Assessed by Molecular Assays. Issue 2 (14th March 2013) - Capuano, Federico; Capparelli, Rosanna; Mancusi, Andrea; Esposito, Salvatore; Corrado, Federica; Guarino, Achille
Abstract The study concerns the presence of Brucella spp. in the stretched curd cheese produced in an area characterized by the presence of a relevant number of herds infected with Brucella spp. One hundred ninety‐one cheese samples made with milk from different species were tested by two molecular assays. Positive samples were further submitted to sequence analysis of the IS711 gene. Eleven out of 98 of the samples made with buffalo milk alone resulted contaminated. The prevalence in cheese samples from cow milk alone and milk from cow and buffalo was 2.7% and 10.5%, respectively. No sample was positive to the microbiological Office International des Epizooties detection tests of Brucella spp. Practical Application The aim of the study is to evaluate the use of molecular assays as a tool to support microbiological and immunological tests carried out to eradicate brucellosis. Molecular assays shows to be a useful aid for the monitoring of herds health and the safety of dairy products evaluation; furthermore, their application to dairy products allows the implementation of the procedures to trace those infected farms that supply milk to dairies.